(untitled) (Journal of Bio-Science, 2015)
Context: To gain a better understanding of the nature of gene action involved in the inheritance of quantitative characters can be obtained through the use of diallel cross analytical approach for the choice of desirable parents and the formulation of an effective breeding programme. Objectives: The aim was to study the nature and magnitude of gene action of inheritance for quantitative traits, length and weight of mature larvae in B. mori through six-parent diallel cross analysis in four rearing seasons Materials and Methods: Six inbred varieties of B. mori were used as parents for a diallel cross. The experiment was conducted in four rearing seasons. Mature larval length (cm) and weight (gm) were collected for statistical analysis. The data were analyzed following the biometrical techniques proposed by Jinks and Hayman (1953), Hayman (1954), Dickinson and Jinks (1956) and Jhonson and Aksel (1964). Results: In the Haymans analysis of variance for length and weight of mature larvae the items a and b were found to be significant against all the three tests of significance. The item b2 was significant for the seasons S-2 and S-3 and the b3 item was significant for all the seasons. The Items c and d were insignificant in all the seasons. The regressions of Wr on Vr for majority of the seasons were significant but did not deviate significantly from unit slope. The varieties Nistari, Nistari oval (G) and NanNung7B of S-1, S-2 and S-4, and Nistari of S-3 for length of larvae and Nistari and Nistari oval (G) of S-1, S-2 and S-3 and Nistari, Nistari oval (G) and Nan Nung 7B of S-4 for larval weight possessed an excess of recessive genes of negative effect. But Nistari oval (G) in S-3 for LL possessed excess of recessive genes with positive effects. On the other hand BSRI-95, BSRI-98 and BV (high) in S-1, S-2 and S-4, and Nan Nung 7B, BSRI-98 and BV(high) in S-3 for LL and BSRI-95, BSRI-98 and BV(high) in S-1, S-2 and S-3, and BSRI-95 and BV(high) in S-4 for LW possessed an excess of dominant genes, which was positive in nature. In S-3 only BSRI-95 for LL and NanNung7B in S-1, S-2 and S-3 and BSRI-98 in S-4 for LW possessed an excess of dominant genes of negative nature. At least one group of dominant genes was involved in controlling these characters. The broad sense heritability was high in all seasons for both the characters whereas the narrow sense heritability was moderate for majority of the seasons except S-3 and S-4 for LW. Conclusion: High heritability, dominant and recessive gene effects suggest that these parents could be used to develop better lines in respect of larval characters investigated in this study and selection programmes will be effective in early generations. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22522 J. bio-sci. 21: 77-87, 2013